Colocutaneous Fistula after Open Inguinal Hernia Repair - Maria Isaia; Demetris Christou; Panayiotis Kallis; Nikolaos Koronakis; Panayiotis Hadjicostas (Case Reports in Surgery)
The plug-and-patch technique is frequently used for the open repair of inguinal hernias; however, serious complications may arise on rare occasions. We present the case of a 69-year-old patient who presented with a colocutaneous fistula with the sigmoid colon 9 years after the repair of a left sliding inguinal hernia with the plug-and-patch technique. The patient underwent sigmoidectomy and excision of the fistulous track. He was discharged on postoperative day 5 and had an uneventful recovery. Although such complications are reported rarely, the surgeon must be aware of them when deciding upon the method of hernia repair.